Data structures and other objects using C++ - Main, Michael; Savitch, Walter (Boston, Massachusetts : Addision-Wesley Publishing Company, 2011)
Data Structures and Other Objects Using C++ takes a gentle approach to the data structures course in C++. Providing an early, self-contained review of object-oriented programming and C++, this text gives students a firm grasp of key concepts and allows those experienced in another language to adjust easily. Flexible by design, professors have the option of emphasizing object-oriented programming, covering recursion and sorting early, or accelerating the pace of the course. Finally, a solid foundation in building and using abstract data types is also provided, along with an assortment of advanced topics such as B-trees for project building and graphs.
The phases of software development -- Abstract data types and C++ classes -- Container classes -- Pointers and dynamic arrays -- Linked Lists -- Software development withtemplates, iterators, and the STL -- Stacks -- Queues -- Recursive Thinking -- Trees -- Balanced trees -- Searching -- Sorting -- Derived classes and inheritance -- Graphs.
Includes index.
Keywords: C++ (COMPUTER PROGRAM LANGUAGE)